Collection Practices of Medicinal Plants Vedic Ayurvedic and Modern Perspectives - Tavhare, Dr Swagata Dilip (International Journal of Pharmaceutical & Biological Archive, 2015)
Collection Practices of Medicinal Plants Vedic Ayurvedic and Modern Perspectives